Gastric Dysmotility and Low Serum Vitamin D Levels in Patients with Gastroparesis - Kedar, A.; Nikitina, Y.; Henry, O. R.; Abell, K. B.; Vedanarayanan, V.; Griswold, M. E.; Subramony, C.; Abell, T. L. (Hormone and Metabolic Research, 2013)
Nutritional abnormalities are common in patients with gastroparesis (Gp), a disorder that may affect gastric motility and may delay emptying. The aim of this work was to identify relationships between serum nutrition markers including 25-OH vitamin D and gastric motility measures in Gp patients. We enrolled 59 consecutive gastric motility clinic patients (48 females, 11 males; mean age 44 years; 42 idiopathic; 17 diabetes mellitus) with Gp symptoms. The 25-OH vitamin D levels, for most patients slightly above the lower limit of normal (96.98 nmol/l±60.99), were lowest in diabetic range (DM) (75.68 nmol/l±34.22) vs. idiopathic (ID) (105.03 nmol/l±67.08) gastroparesis patients. First hour GET: one unit increase in 25-OH vitamin D level was associated 0.11% improvement (95% CI  − 0.22, 0.01 p=0.056) in gastric motility in all patients; this association, although marked in ID Gp patients, ( − 0.13, CI  − 0.25,  − 0.01 p=0.034), was not seen in DM Gp, (0.2, CI  − 0.45, 0.87, p=0.525). Fourth hour GET: Every unit increase of 25-OH vitamin D was associated with significant improvement in all patients, ( 0.11% CI  − 0.23, 0.01, p=0.053), and some weak improvement in ID group, (0.11%  − 0.24, 0.01, p=0.076) and absent in patients with DM (0.03, CI  − 0.66, 0.72, p=0.932). It is concluded that 25-OH vitamin D levels may influence gastric emptying. Underlying mechanisms for this observation might include the impact of 25-OH vitamin D on the health of the enteric nervous system. 25-OH vitamin D contributions to enteric nerve functions should be explored, particularly where autonomic nervous system comorbidities exist.
Keywords: gastroparesis; low vitamins D; gastric emptying test (GET); autonomic nervous system (ANS); diabetes